Manajemen Layanan Khusus - Fitriani Fitriani (JURNAL MAPPESONA, 2023)
Special service management is an activity process where students are provided with the services needed to support the learning process so that educational goals can be achieved. The special services offered by schools to students are generally the same from one school to another. However, the management and utilization process is different. The following are some of the special services provided by schools: library services, health services, dormitory services, guidance and counseling services, laboratory services, cooperative services and school security and parking services.